Sebum lipids influence macrophage polarization and activation4. (28th November 2017) - Lovászi, M.; Mattii, M.; Eyerich, K.; Gácsi, A.; Csányi, E.; Kovács, D.; Rühl, R.; Szegedi, A.; Kemény, L.; Ståhle, M.; Zouboulis, C.C.; Eyerich, S.; et al.
Summary: Background: As lipids are known to regulate macrophage functions, it is reasonable to suppose that a sebocyte–macrophage axis mediated by sebum lipids may exist. Objectives: To investigate if sebocytes could contribute to the differentiation, polarization and function of macrophages with their secreted lipids. Methods: Oil Red O lipid staining and Raman spectroscopy were used to assess the dermal lipid content and penetration. Immunohistochemistry was used to analyse the macrophage subsets. Human peripheral blood monocytes were differentiated in the presence of either supernatant from human SZ95 sebocytes or major sebum lipid components and activated with Propionibacterium acnes . Macrophage surface markers and their capacity to uptake fluorescein isothiocyanate‐conjugated P. acnes were detected by fluorescence‐activated cell sorting measurements. Cytokine protein levels were evaluated by enzyme‐linked immunosorbent assay and Western blot analysis. Results: Sebaceous gland‐rich skin had an increased dermal lipid content vs. sebaceous gland‐poor skin to which all the tested sebum component lipids could contribute by penetrating the dermoepidermal barrier. Of the lipids, oleic acid and linoleic acid promoted monocyte differentiation into alternatively activated macrophages. Moreover, linoleic acid also had an anti‐inflammatory effect in P. acnes‐ activated macrophages, inhibiting the secretion of interleukin (IL)‐1β, IL‐6 and tumour necrosis factor (TNF)‐α. Squalene, palmitic acid, stearic acid and oleic acid augmented the secretion of IL‐1β, even in the absence of P. acnes, whereas oleic acid had a selective effect of inducing IL‐1β but downregulating IL‐6 and TNF‐α secretion. Conclusions: Our results suggest a role for sebaceous glands in modulating innate immune responses via their secreted lipids that are of possible pathological and therapeutic relevance. Abstract : What's already known about this topic? The primary function of human sebaceous glands is to produce and secrete sebum, which, so far, has been considered to only contribute to the lipid barrier of the skin. What does this study add? Our work indicates that sebocyte‐derived lipids may also target macrophage differentiation and activation. Moreover, in the pathogenesis of acne, Propionibacterium acnes –macrophage interaction might be largely dependent on the composition of the sebum, which is of possible pathological and therapeutic relevance. What is the translational message? These findings open several new avenues for research to consider (sebum) lipids, as well as cytokines, in basic and therapeutic research. The analysis of sebum lipid fractions should be addressed from the scope of their potential immunoregulatory functions under various pathological conditions. Plain language summary available online Respond to this article